Immune transcriptional profiles in mothers with clinically elevated depression and anxiety symptoms several years post‐delivery. (27th September 2022) - Nicoloro‐SantaBarbara, Jennifer M.; Carroll, Judith E.; Minissian, Margo; Kilpatrick, Sarah J.; Cole, Steve; Merz, C. Noel Bairey; Accortt, Eynav E.
Abstract: Background: Most research on maternal mental health focuses on the perinatal period and does not extend beyond 12 months postpartum. However, emerging evidence suggests that for some women (30%–50%), psychological symptoms may persist beyond the first year postpartum or even emerge later increasing the risk of chronic mood and anxiety symptoms. Despite the high prevalence rates and devastating maternal‐child consequences, studies examining maternal depression, anxiety, and post‐traumatic stress disorder (PTSD) beyond the first year postpartum are rare and our understanding of the underlying biological mechanisms is incomplete. Inflammatory processes are thought to be involved in the pathophysiology of depression, anxiety, & PTSD outside of the postpartum period. Therefore, the purpose of the current investigation was to examine the relationship between depression, anxiety, and PTSD two to three years post‐delivery, and transcriptional control pathways relevant to inflammatory and antiviral processes. Methods: Women over 18 years of age enrolled in ongoing research studies at Cedars Sinai Medical Center who were 2–3 years postpartum were invited to participate in the current study. Women ( N = 33) reported on their levels of depression, anxiety, and PTSD and provided a blood sample approximately 2–3 years post‐delivery. Bioinformatic analyses of differential gene expression (DGEs) to infer transcription factor activity were used. Gene expression was assayed by RNA sequencing and TELiS bioinformatics analysis of transcription factor‐binding motifs in the promoters of differentially expressed genes. Results: DGE analyses revealed that women with clinically elevated symptoms of depression, anxiety and PTSD ( n = 16) showed upregulation of genes activated by transcription control pathways associated with inflammation (NF‐Κ B, p = 0.004; JUN, p = 0.02), including β‐adrenergic responsive CREB ( p = 0.01) and reduced activation of genes associated with the antiviral response (IRFs, p = 0.02) and the glucocorticoid signaling pathway (GR, p = 0.02) compared to women without clinical symptoms ( n = 17). Conclusions: This is one of the first investigations into the immune signaling pathways involved in depression, anxiety, and PTSD two to three years post‐delivery. The results of this study suggest that clinically elevated symptoms of depression, anxiety, and PTSD two to three years post‐delivery are associated with a gene expression profile characterized by upregulated expression of pro‐inflammatory genes and downregulated expression of antiviral genes. The data also point to two potential stress responsive pathways linking symptoms to increased inflammatory signaling in immune cells: sympathetic nervous system mediated β‐adrenergic signaling and reduced hypothalamic pituitary adrenal axis activity. Together, these findings highlight the need for investigations into maternal mental health beyond the first year postpartum.